The dawn exploration of (4) vesta as the 'ground truth' to interpret asteroid polarimetry - Cellino, A. (2016)
The results of the in situ exploration of the asteroid (4) Vesta by the Dawn spacecraft open new perspectives in the field of interpretation of remote-sensing polarimetric measurements of asteroids. (4) Vesta has long been known to be the only asteroid exhibiting a cyclic variation of the degree of linear polarization of the sunlight scattered by its surface, with a period which is synchronous with the object's rotation. This variation must be the consequence of some heterogeneity of the asteroid's surface, including regions characterized by different albedo, or composition, or regolith properties, or a combination of the above features. For a long time, this kind of conclusion has remained essentially qualitative. Now, after the extensive exploration of Vesta's surface by Dawn, it is possible to interpret the data set of polarimetric measurements of Vesta, including some unpublished data presented here for the first time, in terms of a correspondence between the degree of linear polarization and the variation of local properties of the surface visible to ground-based observers during Vesta's rotation, as seen at different epochs and under different illumination conditions. This makes it possible to refine our knowledge of the empirical relation between polarization properties and albedo, which is commonly used to derive the albedo from remote-sensing measurements of linear polarization of atmosphereless Solar system bodies.